Hubungan Lama Waktu Tidur Dengan Kejadian Obesitas Pada Remaja Di Desa Pulo Ara Kecamatan Kota Juang Kabupaten Bireuen - Devi Maulida; Lina Ekawati; Rahmad Mouliansyah (Indonesia, 2025)
Research conducted in Australia shows that the prevalence of obesity in children aged 5–12 years who sleep <10 hours is 22.3%. Short sleep duration, namely <10 hours, was found to be associated with an increased risk of obesity of 2.61 times greater than children whose sleep duration was ≥10 hours. This study aims to determine the relationship between the length of sleep time and the incidence of obesity in adolescents in Pulo Ara Village, Kota Juang District, Bireuen Regency in 2024. The type of research is analytical research using a cross sectional study approach. The population in this study was teenagers aged 12-16 years, totaling 45 people with a sampling technique that was the total population. Research Results: It was found that the majority of respondents were in the oversleeping category, namely 23 respondents (51.1%), the majority of respondents were in the obesity category I, namely 14 respondents (31.2%), the Chi Square test obtained a value of ρ (0.001) < α (0.05), There is a relationship between sleep duration and the incidence of obesity in adolescents in Pulo Ara Village, Kota Juang District, Bireuen Regency. It is hoped that teenagers can regulate their sleep patterns, maintain their diet and do exercise, so that teenagers do not become obese.